2019
DOI: 10.3892/mmr.2019.10260
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation inhibits the high glucose‑induced EMT of peritoneal mesothelial cells by activating the Nrf2 antioxidant pathway

Abstract: The high glucose (HG)-induced epithelial-mesenchymal transition (EMT) of peritoneal mesothelial cells (PMCs) serves an important role in peritoneal fibrosis (PF) during peritoneal dialysis. Our previous study reported that zinc (Zn) supplementation prevented the HG-induced EMT of rat PMCs in vitro . In the present study, the role of Zn in HG-induced EMT was investigated in vivo using a rat model of PF. Additionally, the molecular mechanisms underlying HG-induced EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…To our knowledge, few data have demonstrated the activation of Nrf2/HO-1 signaling inhibiting ROS production and MMT in HPMCs. However, it was limited to phenomenon observation and lacked mechanism research and efficacy verification [30]. In our study, we illustrated for the first time that asiaticoside can inhibit ROS production by targeting the Nrf2/HO-1 signaling pathway in the PD field.…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, few data have demonstrated the activation of Nrf2/HO-1 signaling inhibiting ROS production and MMT in HPMCs. However, it was limited to phenomenon observation and lacked mechanism research and efficacy verification [30]. In our study, we illustrated for the first time that asiaticoside can inhibit ROS production by targeting the Nrf2/HO-1 signaling pathway in the PD field.…”
Section: Discussionmentioning
confidence: 95%
“…The cells HG + Zn group [HG (126 mM) and ZnSO4 (10 μM)] significantly inhibited the HG‐induced EMT and reversed the HG‐stimulated increase in migration and increase in ROS levels. These data suggest that zinc activates the Nrf2 antioxidant pathway of HG‐induced HPMCs [91].…”
Section: Nutritional Strategies To Mitigate the Inflammationmentioning
confidence: 99%
“…Gao et al. [ 165 ] showed that Zn supplementation can reduce oxidative stress in peritoneal mesothelial cells (PMcs) to inhibit the effect of high glucose (HG) on epithelial-mesenchymal transition (EMT), thereby, improving peritoneal fibrosis (PF) during peritoneal dialysis. Zn deficiency is a predictor of cardiovascular death in dialysis patients [ 166 ], and decrease of Zn levels in dialysis patients is significantly correlated with diastolic dysfunction [ 167 ].…”
Section: Advances In Research On Trace Elements and Malnutritionmentioning
confidence: 99%